2015
DOI: 10.1038/ncomms8692
|View full text |Cite
|
Sign up to set email alerts
|

Significant radiative impact of volcanic aerosol in the lowermost stratosphere

Abstract: Despite their potential to slow global warming, until recently, the radiative forcing associated with volcanic aerosols in the lowermost stratosphere (LMS) had not been considered. Here we study volcanic aerosol changes in the stratosphere using lidar measurements from the NASA CALIPSO satellite and aircraft measurements from the IAGOS-CARIBIC observatory. Between 2008 and 2012 volcanism frequently affected the Northern Hemisphere stratosphere aerosol loadings, whereas the Southern Hemisphere generally had loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
134
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 57 publications
10
134
1
Order By: Relevance
“…As the descent is seen in sulfate aerosol and SO 2 , it is not primarily driven by sedimentation. A similar pattern of subsidence was found by Andersson et al (2015, their Fig. 3) when studying aerosol scattering measured by CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations).…”
Section: Sulfur Transportsupporting
confidence: 80%
See 2 more Smart Citations
“…As the descent is seen in sulfate aerosol and SO 2 , it is not primarily driven by sedimentation. A similar pattern of subsidence was found by Andersson et al (2015, their Fig. 3) when studying aerosol scattering measured by CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations).…”
Section: Sulfur Transportsupporting
confidence: 80%
“…Niemeier and Timmreck, 2015;Rasch et al, 2008). The negative radiative effect of stratospheric aerosol (Andersson et al, 2015;Brühl et al, 2015;Ridley et al, 2014;Santer et al, 2014;Solomon et al, 2011;Vernier et al, 2011) is discussed as being one of the causes of the global warming "hiatus" experienced during the first decade of this century (Haywood et al, 2014;Santer et al, 2014;Fyfe et al, 2013). Hofmann et al (2009) observed an increase in stratospheric aerosol load and suggested that this was due to anthropogenic emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol particles in this region provide surface area for heterogeneous chemistry (Søvde et al, 2007) and influence the formation of ice clouds (Krämer et al, 2009) and thereby in-directly impact the Earth's radiation budget. The discovery of the Asian Tropopause Aerosol Layer (ATAL) by Vernier et al (2011) and the much stronger than previously thought radiative impact of volcanic aerosols in the UT/LMS (Andersson et al, 2015) are just two examples of the importance, but also the limited knowledge, of the UT/LMS aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case for tracking the evolution of aerosol from volcanic eruptions, which can have a substantial effect on the aerosol optical depth in the lowermost stratosphere (Ridley et al, 2014;Andersson et al, 2015). Furthering the understanding of the transport of aerosol near and across the tropopause would also benefit from higher spatial and temporal resolution observations.…”
Section: Introductionmentioning
confidence: 99%